Using Skindex-29 Scale to Assess The Impact of Androgenetic/Patterned Hair Loss on Quality of Life of Patients in Pakistan - Sadiq, Sakina; Naveed, Tehseen; Naveed, Safoora; Minhas, Irfan Jamil; Khan, Bushra Muzaffar; Sadiq, Sunniya (Pakistan Armed Forces Medical Journal, 2022)
Objective: to assess the impact of androgenetic alopecia (AGA)/female patterned hair loss (FPHL) on the quality of life of Pakistani patients using Skindex-29 scale. Study Design: Cross-sectional study. Place and Duration of Study: Outpatient Department of Dermatology, Combined Military Hospital, Lahore Pakistan, from Oct 2020 to Mar 2021. Methodology: Three hundred patients (150 males and 150 females) having androgenetic alopecia (AGA)/female patterned hair loss (FPHL) were selected by consecutive sampling. Skindex-19 questionnaire was used to assess the impact of alopecia on their quality of life. Results: Mean age of study participants was 41.6 ± 12.4 years (range: 18-72 years). Maximum patients (40.7%) had grade-1 severity of alopecia. Most of the patients (37.3%) had disease duration of 1-5 years. Mean global score, symptoms scale score, emotion scale score and function scale score were 31.3 ± 14.8, 22 ± 22.56, 41.67 ± 28.1 and 30 ± 26.5 respectively. Gender and disease duration were statistically significant (p=0.001 and p=0.013 respectively). Conclusion: Skindex-29 can be successfully used in our setup for quality of life studies in AGA/FPHL patients. Females were more severely affected than males as per global scores on Skindex-29.